Attainment and labour market outcomes among young tertiary graduates (Education Indicators in Focus, 2016)
Among 25-34 year-olds with a tertiary degree, the proportion of those who obtained at least a master's or equivalent degree varies from 4% in Chile to 79% in the Slovak Republic. Tertiary attainment also varies across generations: while 49% of tertiary-educated 25-34 year-olds have a bachelor's or equivalent degree as their highest educational attainment, this falls to 39% among 55-64 year-olds. Employment prospects tend to improve with tertiary attainment levels: the average employment rate of 25-34 year-olds with a doctorate is 88%, for those with a master's or equivalent degree it is 84% and for those with at most a short-cycle or a bachelor's degree it is around 80%. In some countries, however, increased tertiary attainment is not associated with improved employment prospects among 25-34 year-olds, except for doctorate holders. In other countries, short-cycle tertiary graduates are more likely to be employed than those with a bachelor's degree